Copolymer microgel latex as well as preparation method and application thereof

The copolymer microgel latex is prepared by emulsion polymerization method, and its composition and structure are regulated, which solves the problem of difficult regulation of the application of copolymer microgels in rubber in the prior art, and realizes the preparation of high-performance vulcanized rubber, which is suitable for tire treads.

CN119552323AActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311133778.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-04
Estimated Expiration
2043-09-04

AI Technical Summary

Technical Problem

The application of existing copolymer microgels in rubber is difficult to regulate the composition, structure and particle size of gel particles, affecting their performance.

Method used

The copolymer microgel latex is prepared by emulsion polymerization method, and the conjugated diene, monovinyl aromatic, vinyl unsaturated carboxylic acid, crosslinked monomer and monomer containing epoxy functional groups are used as monomers. During the polymerization process, the structure and particle size of the particles are adjusted by changing the polymerization formula and adding crosslinked monomers.

Benefits of technology

The flexible regulation of the composition, structure and particle size of the copolymer microgel is achieved. The prepared vulcanized rubber has achieved a good balance in rolling resistance, slip resistance and wear resistance, and is suitable for manufacturing high-performance tire treads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552323A_ABST
    Figure CN119552323A_ABST
Patent Text Reader

Abstract

The invention relates to the field of emulsion polymerization, and discloses copolymer microgel latex as well as a preparation method and application thereof, monomers for forming a copolymer in the copolymer microgel latex comprise a conjugated diene monomer, a monovinyl aromatic monomer, a vinyl unsaturated carboxylic acid monomer, a crosslinking monomer and a monomer containing an epoxy functional group; the surface of the copolymer is grafted with an epoxy monomer. The vulcanized rubber of the rubber composition containing the copolymer microgel achieves better balance in the aspects of rolling resistance, wet skid resistance and wear resistance, and is suitable for manufacturing tread rubber of tires.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of emulsion polymerization, and in particular to a copolymer microgel latex, a method for preparing the copolymer microgel latex, a latex composition, a rubber composition, a vulcanized rubber, and application of the vulcanized rubber in manufacturing tire treads. Background Art

[0002] Copolymer microgel latex can be directly mixed with natural latex or styrene-butadiene latex, and then coprecipitated to make a masterbatch. Due to its large specific surface area, copolymer microgel has more opportunities to react physically and chemically with the base rubber and reinforcing fillers. Compared with inorganic reinforcing fillers, copolymer microgel has the characteristics of low density. When used in rubber, many properties can be improved or enhanced, such as improving the extrusion process performance of the rubber compound (reducing outlet expansion and thermal sag), significantly reducing the rolling resistance of the vulcanized rubber, improving the anti-skid performance, and improving the wear resistance. These properties are particularly important for the production and use of tires, so the application of copolymer microgel in rubber has become a research hotspot in recent years.

[0003] There are several methods for preparing copolymer microgels. One is to add peroxide to the copolymer microgel latex to crosslink the rubber particles in the latex under certain conditions. For example, USP6127488 uses peroxide to crosslink styrene butadiene latex under certain conditions, and the crosslinked styrene butadiene rubber particles are used in NR / BR blended rubber to improve the anti-slip and wear resistance of the NR / BR blended rubber.

[0004] The second is to use high-energy rays to induce crosslinking of rubber particles in latex, i.e., radiation crosslinking. For example, CN103073758A uses radiation crosslinking on nitrile latex to obtain a crosslinked nitrile latex with a particle size of 50-200 nanometers, a gel content of more than 60%, and a homogeneous structure. The crosslinked nitrile latex is mixed with uncrosslinked styrene butadiene latex, and after coagulation, a rubber composition with a weight ratio of crosslinked nitrile rubber particles to uncrosslinked styrene butadiene rubber of 1:99 to 20:80 is obtained. The rolling resistance, anti-slip performance, and wear resistance of the vulcanized rubber of the rubber composition can be improved at the same time, and can be used to prepare high-performance automobile tread rubber. However, the disadvantage of the above two methods is that it is difficult to control the composition, particle structure, and particle size of the gel particles.

[0005] The third method is to directly prepare copolymer microgel latex by emulsion polymerization. The characteristics of this method are that the composition, particle structure and particle size of the copolymer microgel can be flexibly controlled, and the surface of the particles can be grafted and modified by introducing functional monomers containing special functional groups, which can improve the processing and application performance of different rubber compositions. For example, CN104136519A provides a hydroxyl-containing polybutadiene microgel with a glass transition temperature of -70 to -80°C and a gel content greater than 80%, and its tread rubber composition and vulcanized product, which are used to produce winter tires, improve grip on snow and ice, and have high wear resistance and low rolling resistance. Summary of the invention

[0006] The purpose of the present invention is to provide a new copolymer gel latex, so that the tire prepared by the copolymer gel latex has excellent performance, thereby providing a copolymer microgel latex, a method for preparing the copolymer microgel latex, a latex composition, a rubber composition, a vulcanized rubber and the use of the vulcanized rubber in manufacturing tire treads. The vulcanized rubber prepared by using the copolymer gel latex achieves a good balance in rolling resistance, anti-skid property and wear resistance, and is suitable for manufacturing tire treads.

[0007] In order to achieve the above object, the present invention provides a copolymer microgel latex in a first aspect, wherein the copolymer in the copolymer microgel latex contains (a) structural units provided by conjugated diene monomers, (b) structural units provided by monovinyl aromatic monomers, (c) structural units provided by vinyl unsaturated carboxylic acid monomers, (d) structural units provided by crosslinking monomers, and (e) structural units provided by monomers containing epoxy functional groups;

[0008] wherein the structural unit (e) is grafted onto the surface of the copolymer;

[0009] Wherein, based on the total weight of structural units (a)-(e), the content of structural unit (a) is 20-80wt%, the content of structural unit (b) is 15-75wt%, the content of structural unit (c) is 0.1-5wt%, the content of structural unit (d) is 0.1-5wt%, and the content of structural unit (e) is 3-15wt%.

[0010] Preferably, the average particle size of the latex particles in the copolymer microgel latex is 90-200 nm.

[0011] Preferably, the copolymer microgel latex has a gel content of 90 wt% or more.

[0012] The second aspect of the present invention provides a method for preparing a copolymer microgel latex, the method comprising the following steps:

[0013] (1) in the presence of an initiator, an emulsifier, an ethylenically unsaturated carboxylic acid monomer and a portion of a monovinyl aromatic monomer are contacted in a dispersion medium to obtain a latex A;

[0014] (2) continuously adding the conjugated diene monomer, the remaining monovinyl aromatic monomer, the crosslinking monomer and the molecular weight regulator to the latex A obtained in step (1) to react and obtain latex B;

[0015] (3) continuously adding a monomer containing an epoxy functional group to the latex B obtained in step (2) and reacting the monomer to obtain a copolymer microgel latex;

[0016] Among them, based on the total weight of the monomers, the amount of conjugated diene monomer is 20-80wt%, the amount of monovinyl aromatic monomer is 15-75wt%, the amount of vinyl unsaturated carboxylic acid monomer is 0.1-5wt%, the amount of crosslinking monomer is 0.1-5wt%, and the amount of monomer containing epoxy functional group is 3-15wt%.

[0017] The third aspect of the present invention provides a copolymer microgel latex prepared by the preparation method described above.

[0018] The fourth aspect of the present invention provides a latex composition, which comprises the copolymer microgel latex as described above.

[0019] According to a fifth aspect of the present invention, there is provided a rubber composition comprising a solid rubber obtained by coagulating and drying the latex composition as described above.

[0020] A sixth aspect of the present invention provides a vulcanized rubber, which is obtained by vulcanizing the rubber composition as described above.

[0021] A seventh aspect of the present invention provides use of the copolymer microgel latex, latex composition, rubber composition or vulcanized rubber described above in manufacturing tire treads.

[0022] The monomers forming the copolymer in the copolymer microgel latex of the present invention include conjugated diene monomers, monovinyl aromatic monomers, vinyl unsaturated carboxylic acid monomers, crosslinking monomers and monomers containing epoxy functional groups, and the surface of the copolymer is grafted with epoxy monomers; the preparation process adopts an emulsion polymerization method, and the copolymer microgel latex of the present invention is prepared by changing the polymerization formula, adding crosslinking monomers, introducing monomers containing epoxy groups, and adopting preferred process conditions. The copolymer microgel latex has a heterogeneous particle structure, the particle surface contains epoxy groups, the average particle size is preferably 90-200nm, and the gel content is preferably more than 90wt%. It can be used to prepare rubber compositions and vulcanized rubbers. The vulcanized rubbers have achieved a good balance in rolling resistance, anti-slip properties, and wear resistance, and are suitable for manufacturing tire treads. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a microscopic phase transmission electron microscope (TEM) image of the copolymer microgel prepared in Example 1. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] The first aspect of the present invention provides a copolymer microgel latex, wherein the copolymer in the copolymer microgel latex contains (a) structural units provided by conjugated diene monomers, (b) structural units provided by monovinyl aromatic monomers, (c) structural units provided by vinyl unsaturated carboxylic acid monomers, (d) structural units provided by crosslinking monomers, and (e) structural units provided by monomers containing epoxy functional groups;

[0026] wherein the structural unit (e) is grafted onto the surface of the copolymer;

[0027] Wherein, based on the total weight of the structural units (a)-(e), the content of the structural unit (a) is 20-80wt%, for example, it can be 20, 30, 40, 50, 60, 70, 80wt% and any range between any two values, preferably 40-70wt%; the content of the structural unit (b) is 15-75wt%, for example, it can be 15, 20, 30, 40, 50, 60, 70, 75, 99wt% and any range between any two values, preferably 25-50wt%; the content of the structural unit (c) is 0.1-5wt%, for example, it can be 0.1, 0.5, 1 , 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5wt% and any range between any two values, preferably 0.5-3wt%; the content of structural unit (d) is 0.1-5wt%, for example, it can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5wt% and any range between any two values, preferably 0.5-3wt%; the content of structural unit (e) is 3-15wt%, for example, it can be 3, 5, 7, 9, 11, 13, 15wt% and any range between any two values, preferably 4-12wt%.

[0028] The conjugated diene monomer may be a conventional conjugated diene monomer in the art. Preferably, the conjugated diene monomer is a C4-C12 conjugated diene selected from at least one of 1,3-butadiene, isoprene, 1,3-pentadiene, 1,3-hexadiene, phenylbutadiene and 2,3-dimethylbutadiene, preferably a C4-C8 conjugated diene, such as 1,3-butadiene and / or isoprene.

[0029] The monovinyl aromatic monomer may be a conventional monovinyl aromatic monomer in the art. Preferably, the monovinyl aromatic monomer is selected from at least one of styrene, p-methylstyrene, o-methylstyrene, m-methylstyrene, p-tert-butylstyrene, p-methoxystyrene, vinylnaphthalene, α-methylstyrene, 4-tert-butylstyrene, 3,5-diethylstyrene, 3,5-di-n-butylstyrene, 4-n-propylstyrene and 4-dodecylstyrene, preferably at least one of styrene, p-vinyltoluene and α-methylstyrene, and more preferably styrene.

[0030] Preferably, the vinyl unsaturated carboxylic acid monomer is selected from at least one of acrylic acid, methacrylic acid, itaconic acid, maleic acid and fumaric acid, preferably methacrylic acid and / or itaconic acid.

[0031] Preferably, the crosslinking monomer is selected from at least one of diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, neopentyl glycol meth)acrylate, divinylbenzene, divinylnaphthalene, trimellitic acid tripropylene, trivinylbenzene, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and ethoxylated pentaerythritol tetra(meth)acrylate, preferably divinylbenzene and / or trimellitic acid tripropylene.

[0032] Preferably, the monomer containing epoxy functional groups is glycidyl (meth)acrylate.

[0033] Preferably, the copolymer microgel latex further contains a dispersion medium, and more preferably, the dispersion medium is water.

[0034] The total solid content in the copolymer microgel latex can be selected in a wide range, preferably, the total solid content in the copolymer microgel latex is 30wt% or more, more preferably 35-45wt%. The total solid refers to the content of all solid substances in the latex after removing water and volatile components.

[0035] Preferably, the average particle size of the latex particles in the copolymer microgel latex is 90-200 nm. Particle size determination: The particle size is determined using a ZETASIZER 3000HSA laser particle size analyzer from Malvern.

[0036] Preferably, the gel content of the copolymer microgel latex is above 90wt%. The test method of gel content is as follows: extract a certain amount of latex with ethanol and dry it, take about 0.2 grams of dry sample (mass is m1) and put it into a stainless steel mesh cage; immerse the mesh cage in a wide-mouth bottle containing 50mL toluene and let it stand for 24 hours; take out the mesh cage, evaporate the toluene solvent, dry it in a vacuum oven at 100℃ for 2 hours, cool it to room temperature, weigh the mass (m2), then the latex gel mass fraction = m2 / m1.

[0037] Preferably, the particles in the copolymer microgel latex are of a heterogeneous structure, i.e., a core-shell structure. Particle structure test: The particle structure is measured using a Hitachi H-800 transmission electron microscope, and the latex particles are stained with osmium tetroxide.

[0038] The second aspect of the present invention provides a method for preparing a copolymer microgel latex, the method comprising the following steps:

[0039] (1) in the presence of an initiator, an emulsifier, an ethylenically unsaturated carboxylic acid monomer and a portion of a monovinyl aromatic monomer are contacted in a dispersion medium to obtain a latex A;

[0040] (2) continuously adding the conjugated diene monomer, the remaining monovinyl aromatic monomer, the crosslinking monomer and the molecular weight regulator to the latex A obtained in step (1) to react and obtain latex B;

[0041] (3) continuously adding a monomer containing an epoxy functional group to the latex B obtained in step (2) and reacting the monomer to obtain a copolymer microgel latex;

[0042] Wherein, based on the total weight of the monomers, the amount of the conjugated diene monomer is 20-80wt%, for example, 20, 30, 40, 50, 60, 70, 80wt% and any range between any two values, preferably 40-70wt%; the amount of the monovinyl aromatic monomer is 15-75wt%, for example, 15, 20, 30, 40, 50, 60, 70, 75, 99wt% and any range between any two values, preferably 25-50wt%; the amount of the vinyl unsaturated carboxylic acid monomer is 0.1-5wt%, for example, 0.1, 0.5, 1, 1 The amount of crosslinking monomer is 0.1-5wt%, for example, it can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5wt% and any range between any two values, preferably 0.5-3wt%, the amount of monomer containing epoxy functional group is 3-15wt%, for example, it can be 3, 5, 7, 9, 11, 13, 15wt% and any range between any two values, preferably 4-12wt%. It should be understood that the total weight of monomers refers to the total weight of conjugated diene monomers, monovinyl aromatic monomers, vinyl unsaturated carboxylic acid monomers, crosslinking monomers and monomers containing epoxy functional groups.

[0043] The types of the monomers are described in the first aspect and will not be described in detail here.

[0044] Preferably, the weight ratio of the portion of the monovinyl aromatic monomer in step (1) to the remaining portion of the monovinyl aromatic monomer in step (2) is 1:1-8, for example, it can be 1:1, 1:2, 1:4, 1:6, 1:8 and any range between any two values, more preferably 1:2-6.

[0045] Preferably, the initiator is a water-soluble persulfate and / or an organic peroxide. The water-soluble persulfate is preferably selected from at least one of potassium persulfate, sodium persulfate and ammonium persulfate. The organic peroxide is preferably selected from at least one of benzoyl peroxide, tert-butyl hydroperoxide, cumene peroxide and dicumyl peroxide.

[0046] Preferably, based on the total weight of the monomers, the amount of the initiator is 0.1-0.5 wt%, for example, 0.1, 0.2, 0.3, 0.4, 0.5 wt% and any range between any two values.

[0047] Preferably, the emulsifier is an anionic surfactant and / or a nonionic surfactant, preferably selected from at least one of fatty acid soap (e.g., fatty acid soap of C12-C20, such as soap salt of lauric acid, myristic acid, palmitic acid or stearic acid, such as potassium stearate), rosin acid soap (e.g., potassium disproportionated rosin acid, etc.), alkyl sulfate (e.g., sodium dodecyl sulfate, etc.), alkyl sulfonate (e.g., sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, etc.), and fatty alcohol polyoxyethylene ether (e.g., fatty alcohol polyoxyethylene ether of C12-18). Those skilled in the art can select as needed.

[0048] Preferably, based on the total weight of the monomers, the amount of the emulsifier is 1-8wt%, for example, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 7, 8wt% and any range between any two values, preferably 1.5-5wt%.

[0049] Preferably, the molecular weight regulator is n-dodecyl mercaptan and / or tert-dodecyl mercaptan.

[0050] Preferably, based on the total weight of the monomers, the amount of the molecular weight regulator is 0.1-1 wt%, for example, 0.1, 0.2, 0.4, 0.6, 0.8, 1 wt% and any range between any two values.

[0051] Preferably, the dispersion medium is water.

[0052] The amount of the dispersion medium can be selected within a wide range. Preferably, based on the total weight of the monomers, the amount of the dispersion medium is 100-250 wt%.

[0053] Preferably, in step (1), the contact conditions include a contact temperature of 60-70° C. and a contact time of 0.3-1.5 hours.

[0054] Preferably, in step (1), the contacting conditions are such that the average particle size of latex A is 50-60 nm.

[0055] Preferably, in step (2), the continuous addition time is 2-6 hours, and the reaction temperature is 75-90°C.

[0056] Preferably, in step (3), the continuous addition time is 0.5-2 hours, the reaction temperature is 85-100° C., and the reaction time is 1-3 hours.

[0057] Preferably, the method further comprises adding a chelating agent to the contact reaction system in step (1).

[0058] Preferably, the chelating agent is selected from at least one of ethylenediaminetetraacetic acid disodium salt, ethylenediaminetetraacetic acid trisodium salt and ethylenediaminetetraacetic acid tetrasodium salt.

[0059] Preferably, the amount of the chelating agent is 0.01-0.1 wt % based on the total weight of the monomers.

[0060] The third aspect of the present invention provides a copolymer microgel latex prepared by the preparation method described above.

[0061] For the description of the latex, see the first aspect.

[0062] The fourth aspect of the present invention provides a latex composition, which comprises the copolymer microgel latex as described above.

[0063] Preferably, the latex composition further contains a second latex. The second latex may be a conventional latex in the art, and preferably, the second latex is natural latex and / or styrene-butadiene latex.

[0064] Preferably, in the latex composition, based on solid content, the content of the copolymer microgel latex is 1-5 wt %, and the content of the second latex is 95-99 wt %.

[0065] The latex composition can be prepared into solid rubber by conventional methods in the art, such as coagulation and drying. Those skilled in the art can operate in the conventional manner in the art, which will not be described in detail herein.

[0066] According to a fifth aspect of the present invention, there is provided a rubber composition comprising a solid rubber obtained by coagulating and drying the latex composition as described above.

[0067] The rubber composition may further contain other additives, such as a vulcanizing agent, a vulcanization accelerator, a reinforcing agent, an activator, and the like.

[0068] A sixth aspect of the present invention provides a vulcanized rubber, which is obtained by vulcanizing the rubber composition as described above.

[0069] The method of vulcanizing the rubber composition can be a conventional choice in the art, which is well known to those skilled in the art and will not be described in detail here.

[0070] A seventh aspect of the present invention provides use of the copolymer microgel latex, latex composition, rubber composition or vulcanized rubber described above in manufacturing tire treads.

[0071] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.

[0072] The copolymer microgel latex in the examples was tested for performance indicators according to the following methods.

[0073] Particle size was measured using a ZETASIZER 3000HSA laser particle size analyzer from Malvern.

[0074] Glass transition temperature was measured by differential scanning calorimetry (DSC).

[0075] Particle structure test: The particle structure was tested using a Hitachi H-800 transmission electron microscope, and the latex particles were stained with osmium tetroxide.

[0076] The test method for gel content is: extract a certain amount of latex with ethanol and then dry it, take about 0.2 grams of dry sample (mass is m1) and put it into a stainless steel mesh cage; immerse the mesh cage in a wide-mouth bottle containing 50mL of toluene and let it stand for 24 hours; take out the mesh cage, evaporate the toluene solvent, dry it in a vacuum oven at 100°C for 2 hours, cool to room temperature, and weigh the mass (m2), then the latex gel mass fraction = m2 / m1.

[0077] Epoxy-containing monomer content (%); The rubber was purified by dissolving it in toluene and reprecipitating it from methanol, and this procedure was repeated twice, followed by titration according to the Jay method [RR Jay; Analytical Chemistry, 36667 (1964)].

[0078] In the following examples, "phm" represents the mass fraction of the substance relative to 100 mass fractions of the total weight of monomers.

[0079] Examples 1-4

[0080] This example is used to illustrate the preparation of the copolymer microgel latex of the present invention.

[0081] The types of monomers and the addition methods for preparing the copolymer microgel latex are shown in Table 1, wherein the amount of each component in the table is in wt%.

[0082] (1) adding 150 phm of deionized water, 2.0 phm of potassium disproportionate rosin acid, 2.0 phm of potassium stearate, 0.05 phm of tetrasodium ethylenediaminetetraacetic acid, and monomers styrene and methacrylic acid required for the first step reaction into a polymerization kettle, setting the temperature of the polymerization kettle to 65° C., adding 0.3 phm of potassium persulfate, and reacting for 30 minutes to prepare a copolymer latex having an average particle diameter of about 50-60 nm and a glass transition temperature of 100° C.;

[0083] (2) continuously adding the monomers styrene, butadiene, tripropylene trimellitate and 0.5 phm of tert-dodecyl mercaptan required for the second step reaction to the material after the first step reaction, setting the polymerization kettle temperature to 80° C., and continuously adding the monomers for 4 hours to obtain a microgel latex with a heterogeneous structure;

[0084] (3) continuously adding glycidyl methacrylate, a monomer required for the third step reaction, to the material after the second step reaction, the temperature of the polymerization kettle was set at 90° C., and the monomer was continuously added for 1 hour; the temperature of the polymerization kettle was set at 95° C., and the reaction was continued for 2 hours to obtain a copolymer microgel latex with epoxy groups grafted on the surface, and the polymerization conversion rate was about 100%.

[0085] Table 1

[0086]

[0087] Figure 1 This is a microscopic phase transmission electron microscope (TEM) picture of the copolymer microgel prepared in Example 1. From this picture, it can be seen that the polymer particles have a heterogeneous structure, wherein the light-colored area is polystyrene and the dark-colored area is a butadiene and styrene copolymer.

[0088] The obtained gel was subjected to performance tests, and the test results are shown in Table 2.

[0089] Table 2

[0090] performance Example 1 Example 2 Example 3 Example 4 Average particle size, nm 162 125 128 97 Gel content, % 97 94 91 91 Epoxy group content, % 4.6 4.7 9.4 4.9

[0091] Application Examples

[0092] 1. The data in the application example are measured using the following instruments and test methods:

[0093] (1) Rolling resistance: The rolling power loss was measured using an RSS-II rubber rolling resistance tester (Beijing Wanhui Yifang Technology Development Co., Ltd.).

[0094] Rolling resistance index (%): The rolling resistance value of pure rubber is taken as the base number, and the percentage of the rolling resistance value of other modified rubber to the rolling resistance value of pure rubber is the rolling resistance index.

[0095] (2) Wear resistance test: According to GB / T 1689-1998, the wear value of the vulcanized rubber was measured using a WML-76 Akron abrasion tester.

[0096] Wear index (%): Taking the wear volume value of pure rubber as the basis, the wear volume value of modified rubber as the percentage of the wear volume value of pure rubber is the wear index.

[0097] (3) Dynamic mechanical properties test (wet slip): The test was conducted using a DMTA IV (dynamic mechanical thermal analyzer) produced by Rheometric Scientific, Inc., USA. The test conditions were 10 Hz, 0.5% strain, and a heating rate of 2°C / min.

[0098] The friction of rubber on a wet surface is related to hysteresis loss, and tanδ at 0°C is usually used to characterize the anti-skid performance. The larger the tanδ value at 0°C, the better the traction performance of the tire on wet roads.

[0099] Anti-skid index (%): The anti-skid value of tanδ of pure rubber is taken as the base number, and the percentage of the anti-skid value of modified rubber to the anti-skid value of pure rubber is the anti-skid index.

[0100] (4) Mechanical properties: measured in accordance with relevant standards.

[0101] 2. Raw materials used:

[0102] Emulsion polybutadiene styrene latex 1502: solid content 20%, styrene binding amount 23wt%, Mooney viscosity 45, produced by Sinopec Qilu Branch; sulfuric acid, sodium hydroxide, CA coagulant, carbon black N234, zinc oxide, stearic acid, sulfur, and accelerator TBBS are all commercially available products.

[0103] 3. Co-coagulation method of copolymer microgel latex and styrene-butadiene latex 1502

[0104] The copolymer gel latex and styrene butadiene latex 1502 are mixed at a certain solid content ratio, and the weight ratio of the solid content of the copolymer microgel latex to the solid content of styrene butadiene latex 1502 is 3:97. The latex mixture is heated to 55±5℃, and the mixed solution of sulfuric acid and CA coagulant is added to the latex, and stirred vigorously. The pH of the latex is controlled at 3.5±0.3 by adjusting the amount of sulfuric acid added. After coagulation, part of the slurry is filtered off, the temperature is raised to 60±5℃, and NaOH solution is added to adjust the pH to 5.3±0.3. Filter, wash with water, and dry to obtain solid rubber.

[0105] 4. Preparation and vulcanization method of rubber compound

[0106] A process:

[0107] The process is carried out in a 1.57L Banbury mixer (product of Farrell Company, UK), with a filling factor of 0.7 and 80°C / 80 rpm; the process is as follows: adding styrene-butadiene rubber raw rubber or a combination of the copolymer microgel of the present invention and styrene-butadiene rubber, carbon black and other additives (except sulfur and accelerator), lowering the top bolt, mixing for 3 minutes, and discharging the rubber (temperature is 150-160°C).

[0108] Two-stage process:

[0109] The formula of the rubber compound is shown in Table 3, and the units are parts by weight.

[0110] After adding sulfur and accelerator, the masterbatch was thinned six times on an XK-160 open mill (Shanghai Rubber Machinery Factory) and then cut into sheets. Then, the masterbatch was cured at 160°C for a period of time T 90 After vulcanization, the vulcanized rubber samples were made into standard specimens and various mechanical property tests were performed. The results are shown in Table 4.

[0111] Comparative Example 1

[0112] The latex was changed from a mixture of two latexes to a single styrene-butadiene latex 1502. The rest was the same as in the application example. The specific rubber compound formula composition is shown in Table 3, and the vulcanized rubber properties are shown in Table 4.

[0113] Table 3

[0114]

[0115]

[0116] Table 4

[0117]

[0118] From the results in Table 4, it can be seen that the rubber composition modified by the copolymer microgel of the present invention has a good balance in rolling resistance, wet skid resistance and wear resistance, and is suitable for manufacturing tire tread rubber.

[0119] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A copolymer microgel latex, characterized in that: The copolymer in the copolymer microgel latex contains (a) structural units provided by conjugated diene monomers, (b) structural units provided by monovinyl aromatic monomers, (c) structural units provided by vinyl unsaturated carboxylic acid monomers, (d) structural units provided by crosslinking monomers, and (e) structural units provided by monomers containing epoxy functional groups; wherein the structural unit (e) is grafted onto the surface of the copolymer; Wherein, based on the total weight of structural units (a)-(e), the content of structural unit (a) is 20-80wt%, the content of structural unit (b) is 15-75wt%, the content of structural unit (c) is 0.1-5wt%, the content of structural unit (d) is 0.1-5wt%, and the content of structural unit (e) is 3-15wt%.

2. The copolymer microgel latex according to claim 1, wherein The conjugated diene monomer is a C4-C12 conjugated diene, preferably at least one selected from 1,3-butadiene, isoprene, 1,3-pentadiene, 1,3-hexadiene, phenylbutadiene and 2,3-dimethylbutadiene, more preferably 1,3-butadiene and / or isoprene; and / or The monovinyl aromatic monomer is at least one selected from styrene, p-methylstyrene, o-methylstyrene, m-methylstyrene, p-tert-butylstyrene, p-methoxystyrene, vinylnaphthalene, α-methylstyrene, 4-tert-butylstyrene, 3,5-diethylstyrene, 3,5-di-n-butylstyrene, 4-n-propylstyrene and 4-dodecylstyrene, preferably at least one selected from styrene, p-vinyltoluene and α-methylstyrene, more preferably styrene; and / or The vinyl unsaturated carboxylic acid monomer is selected from at least one of acrylic acid, methacrylic acid, itaconic acid, maleic acid and fumaric acid, preferably methacrylic acid and / or itaconic acid; and / or The crosslinking monomer is selected from at least one of diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, neopentyl glycol meth)acrylate, divinylbenzene, divinylnaphthalene, trimellitic acid tripropylene, trivinylbenzene, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and ethoxylated pentaerythritol tetra(meth)acrylate, preferably divinylbenzene and / or trimellitic acid tripropylene; and / or The monomer containing epoxy functional groups is glycidyl (meth)acrylate.

3. The copolymer microgel latex according to claim 1 or 2, wherein Based on the total weight of structural units (a)-(e), the content of structural unit (a) is 40-70wt%, the content of structural unit (b) is 25-50wt%, the content of structural unit (c) is 0.5-3wt%, the content of structural unit (d) is 0.5-3wt%, and the content of structural unit (e) is 4-12wt%.

4. The copolymer microgel latex according to any one of claims 1 to 3, wherein The copolymer microgel latex further contains a dispersion medium, preferably, the dispersion medium is water; Preferably, the total solid content of the copolymer microgel latex is above 30 wt %, more preferably 40-50 wt %.

5. The copolymer microgel latex according to any one of claims 1 to 4, wherein The average particle size of the latex particles in the copolymer microgel latex is 90-200 nm; and / or The copolymer microgel latex has a gel content of 90 wt % or more; and / or The particles in the copolymer microgel latex are of a heterogeneous structure.

6. A method for preparing a copolymer microgel latex, characterized in that: The method comprises the following steps: (1) in the presence of an initiator, an emulsifier, an ethylenically unsaturated carboxylic acid monomer and a portion of a monovinyl aromatic monomer are contacted in a dispersion medium to obtain a latex A; (2) continuously adding the conjugated diene monomer, the remaining monovinyl aromatic monomer, the crosslinking monomer and the molecular weight regulator to the latex A obtained in step (1) to react and obtain latex B; (3) continuously adding a monomer containing an epoxy functional group to the latex B obtained in step (2) and reacting the monomer to obtain a copolymer microgel latex; Wherein, based on the total weight of the monomers, the amount of the conjugated diene monomer is 20-80wt%, the amount of the monovinyl aromatic monomer is 15-75wt%, the amount of the vinyl unsaturated carboxylic acid monomer is 0.1-5wt%, the amount of the crosslinking monomer is 0.1-5wt%, and the amount of the monomer containing the epoxy functional group is 3-15wt%; Preferably, based on the total weight of the monomers, the amount of the conjugated diene monomer is 40-70wt%, the amount of the monovinyl aromatic monomer is 25-50wt%, the amount of the vinyl unsaturated carboxylic acid monomer is 0.5-3wt%, the amount of the crosslinking monomer is 0.5-3wt%, and the amount of the monomer containing the epoxy functional group is 4-12wt%; Preferably, the weight ratio of the part of the monovinyl aromatic monomer in step (1) to the remaining part of the monovinyl aromatic monomer in step (2) is 1:1-8, more preferably 1:2-6.

7. The preparation method according to claim 6, wherein: The initiator is a water-soluble persulfate and / or an organic peroxide, wherein the water-soluble persulfate is preferably selected from at least one of potassium persulfate, sodium persulfate and ammonium persulfate, and the organic peroxide is preferably selected from at least one of benzoyl peroxide, tert-butyl hydroperoxide, cumene peroxide and dicumyl peroxide; and / or The emulsifier is an anionic surfactant and / or a nonionic surfactant, preferably at least one selected from fatty acid soap, rosin acid soap, alkyl sulfate, alkyl sulfonate and fatty alcohol polyoxyethylene ether; and / or The molecular weight regulator is n-dodecyl mercaptan and / or tert-dodecyl mercaptan; and / or The dispersion medium is water.

8. The preparation method according to claim 6 or 7, wherein: Based on the total weight of the monomers, the amount of the initiator is 0.1-0.5 wt%; and / or Based on the total weight of the monomers, the amount of the emulsifier is 1-8 wt%; and / or Based on the total weight of the monomers, the amount of the molecular weight regulator is 0.1-1wt%; and / or Based on the total weight of the monomers, the amount of the dispersion medium is 100-250 wt%.

9. The preparation method according to any one of claims 6 to 8, wherein: In step (1), the contact conditions include a contact temperature of 60-70° C. and a contact time of 0.3-1.5 hours. In step (2), the continuous addition time is 2-6 hours, and the reaction temperature is 75-90°C; In step (3), the continuous addition time is 0.5-2 hours, the reaction temperature is 85-100° C., and the reaction time is 1-3 hours.

10. The preparation method according to any one of claims 6 to 9, wherein: The method further comprises adding a chelating agent to the contact reaction system in step (1); Preferably, the chelating agent is selected from at least one of ethylenediaminetetraacetic acid disodium salt, ethylenediaminetetraacetic acid trisodium salt and ethylenediaminetetraacetic acid tetrasodium salt; Preferably, the amount of the chelating agent is 0.01-0.1 wt % based on the total weight of the monomers.

11. The copolymer microgel latex prepared by the preparation method according to any one of claims 6 to 10.

12. A latex composition, characterized in that The latex composition comprises the copolymer microgel latex according to any one of claims 1 to 5 and 11; Preferably, the latex composition further comprises a second latex; More preferably, the second latex is natural latex and / or styrene-butadiene latex; More preferably, in the latex composition, based on solid content, the content of the copolymer microgel latex is 1-5 wt %, and the content of the second latex is 95-99 wt %.

13. A rubber composition, characterized in that: The rubber composition comprises a solid rubber obtained by coagulating and drying the latex composition according to claim 12.

14. A vulcanized rubber, characterized in that: The vulcanized rubber is obtained by vulcanizing the rubber composition according to claim 13.

15. Use of the copolymer microgel latex according to any one of claims 1 to 5 and 11, the latex composition according to claim 12, the rubber composition according to claim 13 or the vulcanized rubber according to claim 14 in manufacturing tire treads.

Citation Information

Patent Citations

  • Rubber composition, preparation method thereof, and vulcanized rubber thereof

    CN103073758A

  • Microgel-containing tread mixture for winter tyres

    CN104136519A

  • Compositions containing NBR-based microgels

    CN107428883A

  • Sealing gels, process for production thereof and use thereof in sealing compounds for self-sealing tyres

    CN107849182A

  • Polymer latex for elastomeric film preparation having excellent stress retention properties and softness

    CN114430749A